Foreigners working in Icelandic pre-schools - Johanna Ann-Louise Carin Läärä (2010)
Iceland has faced a sudden rush of immigrants due to the economic bloom before autumn 2008 (Statistics Iceland, 2009a). Many immigrants are educated but they cannot work in the occupations that they are educated for because of their Icelandic language skills. As the language seems to be the key to the Icelandic society, many started to work in pre-schools in order to learn the language. Working with young children is not easy when one doesn’t speak the language at all or just a bit of it. Also, cultural differences might cause some issues in work-life and the close social circles at pre-schools where the others might have worked for a long time are almost impenetrable. The purpose of this qualitative research is to find out the reasons why foreigners chose to work in pre-schools, what kind of possible problems they have faced if any or they are still facing and how they solved the problems if they occurred and overcome the difficulties.